Oliver Clegg - Price, Matt (Anomie Publishing, 2016)
An eclectic, polyphonic and interdisciplinary artist, Clegg's oeuvre stretches from painting, drawing and printmaking to sculpture, installation and beyond. With his erudite, surprising and striking repertoire, and his diverse materials and methods of fabrication, Clegg offers the viewer a complex, sometimes playful, other times moving journey into existential and ontological notions of objecthood and matter, images and signs, language and communication, creation and being--
Includes index
Includes artist's chronology
Keywords: Clegg, Oliver / Criticism and interpretation; Criticism, interpretation, etc; Bildband